International climate change policy: triggering environmental reforms in the European electricity sector. (24th February 2004) - Ringel, Marc
International climate change policy has come to a relative standstill with most of the countries being discouraged by the high costs of actively pursued climate policy measures. However, climate change policy offers ancillary benefits for proactive stakeholders like the European Union, in addition to the main benefit of mitigating climate change. This article takes a closer look at ancillary benefits the EU hopes to retrieve from its active climate change policy in the field of energy policy. The analysis is limited to the electricity sector, in which the highest potentials for emission abatement can be expected. It shows that most reduction potentials can be realised by using win-win measures, supporting aims of both climate change and energy policies. Generalising this finding, this review points out that ancillary benefits should be emphasised more than before as an incentive for an actively pursued global environmental policy.